Identification of the activity source of CO2 electroreduction by strategic catalytic site distribution in stable supramolecular structure system. Issue 3 (31st August 2020) - Sun, Sheng-Nan; Li, Ning; Liu, Jiang; Ji, Wen-Xin; Dong, Long-Zhang; Wang, Yi-Rong; Lan, Ya-Qian
Abstract: Identification of the real catalytic site in CO2 reduction reaction (CO2 RR) is critical for the rational design of catalysts and the understanding of reactive mechanisms. In this study, the catalytic activity of pyridine-containing materials was for the first time structurally demonstrated in CO2 RR by crystalline supramolecular coordination compounds model system. The system consists of three stable supramolecular coordination compounds (Ni-TPYP, Ni-TPYP-1 and Ni-TPP) with different numbers (4, 2 and 0) of active pyridine groups (i.e. uncoordinated pyridine nitrogen atoms). The electrocatalytic test results show that with the decrease of the number of active pyridine groups, the CO2 RR performance is gradually reduced, mainly showing the reduction of highest FECO (99.8%, 83.7% and 25.6%, respectively). The crystallographic, experimental and theoretical evidences prove that the CO2 RR activity is more likely derived from uncoordinated pyridine nitrogen than the electrocatalytic inert metal nickel in porphyrin center. This work serves as an important case study for the identification of electrocatalytic activity of pyridine-containing materials in CO2 RR by simple supramolecular model system. Abstract : The catalytic activity of pyridine-containing materials was for the first time structurally demonstrated in CO2 reduction reaction by supramolecular and coordination compounds structure model system including Ni-TPP, Ni-TPYP and Ni-TPYP-1.